Improving Learning Outcomes of Simple Arithmetic Using Smart Ladder Media for Second Grade Elementary School - Destiani, Puji (Prosiding University Research Colloquium, 2021)
This study aims to determine the increase in learning outcomes of simple arithmetic operations using smart ladder media. This study was conducted towards 2nd-grade elementary school students. The data collection was from findings of scientific articles obtained from journals with qualitative methods. From the data obtained that using smart ladder media can significantly improve learning outcomes of simple arithmetic operations. Student learning outcomes increase, namely from the first cycle, the completeness value of 51 % and 78% completeness value in the cycle. It can be concluded that the use of learning ladder media can improve mathematical arithmetic operations.